IDENTIFIKASI PARASIT PADA IKAN LELE (Clarias sp.) DI KOLAM BUDIDAYA IKAN KABUPATEN BANGKA - Rani Tuwitri; Riko Irwanto; Andri Kurniawan (Fakultas Perikanan dan Ilmu Kelautan, 2020)
The presence of parasites has a negative effect on catfish (Clarias sp.) in the form of disease in its host. Parasites based on their environment or habitat can be divided into two, namely ectoparasites (parasites that live on the outer body surface of the host) and endoparasites (parasites that live inside the host’s body). This study aims to identify the type and analyze the prevalence level of parasites infecting catfish in the Fish Farms in Balunijuk Village and Petaling Banjar Village, Bangka Regency. This research was conducted in October-November 2020. The method used was a descriptive survey in the form of a purposive sampling method. Fish samples were taken from two stations, with each station taking two samples. Twenty fish samples were taken at each station. The results showed that there were 4 identified parasitic phyla, i.e. phylum Ciliophora consisted of Vorticella sp. and Stylonychia sp., Phylum Protozoa consisting of Blastodiniidae. Phylum Platyhelminthes consisting of Dactylogyrus sp., Gyrodactylus sp., and Ligula intestinalis., Phylum Nemathelminthes consisting of Camallanidae. The results showed that the highest prevalence level was found in Dactylogyrus sp., while the highest level of intensity and dominance was found in Blastodiniidae.